Spatial Distribution of Euschistus heros (Hemiptera: Pentatomidae) in Cotton (Gossypium hirsutum Linnaeus) - WEBER,ANDERSON C. (2018)
Abstract Recently, the Neotropical brown stink bug, Euschistus heros (Pentatomidae: Hemiptera), has been detected in cotton in the Brazilian Cerrado. Several reliable surveys have been conducted on the spatial distribution of stink bugs in soybean; however, few studies have examined the behavior of this insect in cotton in Brazil. Thus, this study examined the spatial distribution of E. heros in cotton using aggregation indices based on the variance-to-mean ratio, Morisita index, exponent k, Poisson and negative binomial distributions. Inverse Distance Weighting interpolation maps were also used to represent insect density. The study was conducted in a 1.1 hectare experimental cotton field in which 64 equally-sized plots were sampled on a weekly basis. Our findings revealed that stink bugs presented an aggregate distribution in 2 sampling weeks based on aggregation indices, and this pattern was best described by a negative binomial distribution. Maps showing the density of pests can be an important tool for sampling pests in crops and control measures in early stages of infestation, when there is an edge effect on the distribution of E. heros, can be an efficient strategy in cotton.